Cervical Laminectomy for the Treatment of Chronic Caudal Cervical Spondylomyelopathy in a Dog - Sembenelli, Guilherme [UNESP]; Nery Wittmaack, Monica Carolina [UNESP]; Oliveira, Levi [UNESP]; Moraes, Paola Castro [UNESP]; Minto, Bruno Watanabe [UNESP]; Gosuen Goncalves Dias, Luis Gustavo [UNESP] (Univ Fed Rio Grande Do Sul, 2016)
Background: Cervical spondylomyelopathy (CSM) is a common disease of the cervical spine, and causes neurogenic disorders commonly diagnosed in large and giant breeds dogs. There are many surgical procedures proposed for the treatment of CSM. Although many authors report a high success rate (between 70% and 90%) after surgical procedures, the high number of techniques described reflects the difficulty in treating this disorder. The objective of this paper is to report a case of CSM with chronic ventral compression (intervertebral disc extrusion) that was treated with dorsal decompression, and to demonstrate the effectiveness of the decompressive technique through pre-and post-operative myelograms. Case: A 9-year-old Doberman Pinscher dog weighing 41.8 kg presented due to a history of tetraparesis. Neurological examination did not reveal any alteration in mental status. There was absence of conscious proprioception on the four limbs; the pelvic limbs were more severely affected. Bilateral patellar hyperreflexia and normal flexor withdrawal reflex were observed on the hind limbs. There was decreased flexor withdrawal reflex and increased extensor tone on the forelimbs. The patient exhibited pain during caudal cervical palpation, and no alterations were seen on the cutaneous trunci reflex. Superficial pain was absent in the hind limbs; forelimbs exhibited presence of motor function with severe paresis. Survey radiographs revealed intervertebral disc space narrowing between C6-C7. A myelogram revealed ventral and dorsal compressions of the spinal cord in the C6-C7 area. Surgical treatment was elected, and laminectomy of the sixth and seventh cervical vertebrae was performed. Improvements were progressive on evaluations made on the seventh, eighteenth, forty-fifth, and sixtieth days after surgery. On the forty-fifth day after surgery, the patient was able to walk with the aid of a support sling, but was incapable of standing and walking without help. Muscle atrophy and paresis progressively improved up to the sixtieth day after surgery, but such improvement was not enough for the patient to get up and walk without the aid of the sling. In view of the evolution of the clinical signs during the post-operative period, another myelogram was performed to check if the extruded intervertebral disc, which was not removed during laminectomy, was still causing spinal cord compression. In comparison to the first myelogram, the compression was significantly attenuated by the surgical procedure. In this examination, the contrast medium columns were minimally compromised by the presence of herniated material; because of that, we opted not to perform a second surgical intervention for removal of herniated disc content. Discussion: Cervical laminectomy is indicated primarily for cases of dorsal compression associated with osteoarthritic changes of facet joints, malformation of the dorsal lamina, or ligamentum flavum hypertrophy however, this technique has also been used to treat ventral compressions, especially if they are multiple. There are no reports of direct comparison between laminectomy and other surgical techniques for the treatment of chronic ventral compressions; consequently, the choice of the technique depends on the surgeon's experience and preference. Some authors argue that cervical laminectomy is not enough to attenuate the compression caused by the disc because this technique does not allow removal of the herniated disc material located ventrally. However, in the case reported here, a comparison between pre-and postoperative myelograms revealed that even though the herniated material was not removed, dorsal decompression allowed dorsal dislocation of the spinal cord and, consequently, promoted considerable attenuation of ventral compression.
Keywords: Wobbler syndrome; nervous system; spinal cord; cervical vertebrae